CHEMICAL IMMOBILIZATION AND HEMATOLOGYC AND ENDOPARASITOLOGIC EVALUATION OF LEOPARDUS COLOCOLO IN KHASTOR, POTOSÍ, BOLIVIA - Beltrán S., L. Fabián (2009)
In May 2005 and April 2006, in the region of Khastor, Potosi, Bolivia, a female pampas cat (Leopardus colocolo) was captured. The efficacy of a protocol for chemical immobilization for animal handling, clinical evaluation and collection of biological samples was evaluated. It was used ketamine hydrochloride (KH) + medetomidine hydrochloride (MH), and antagonized the latter with atipamezole (AH). In 2005 were administered 4.38 mg/kg of KH + 0.04 mg/kg of MH, requiring 2 successive doses of 1.76 mg/kg of KH. In 2006 were administered 5.0 mg/kg of KH + 0.05 mg/kg of MH. MH was antagonized with 0.22 and 0.25 mg/kg of AH in 2005 and 2006 respectively. The induction time and chemical immobilization in both campaigns were very similar but the recovery time from anesthesia in 2006 was shorter than in 2005. The clinical evaluation indicated adequate health and physical status. The hemograms showed values within the normal range for domestic felines. Eggs of Toxascaris leonina and Uncynaria sp. were found.